2016
DOI: 10.1016/j.jip.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Identifying bacterial predictors of honey bee health

Abstract: Non-targeted approaches are useful tools to identify new or emerging issues in bee health. Here, we utilise next generation sequencing to highlight bacteria associated with healthy and unhealthy honey bee colonies, and then use targeted methods to screen a wider pool of colonies with known health status. Our results provide the first evidence that bacteria from the genus Arsenophonus are associated with poor health in honey bee colonies. We also discovered Lactobacillus and Leuconostoc spp. were associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…The position of the honey bee Arsenophonus on the parasitism-mutualism continuum remains speculative. Our observations of HT, systemic infections and a higher prevalence among dead hosts strengthens interpretations of previous work correlating Arsenophonus with poor health outcomes in bees [44,45,91]. HT is considered to increase the scope for the evolution of virulence [17,18], although this trait alone is insufficient to draw conclusions regarding symbiont phenotype, as many avirulent or beneficial microbes are transmitted horizontally [15,92].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The position of the honey bee Arsenophonus on the parasitism-mutualism continuum remains speculative. Our observations of HT, systemic infections and a higher prevalence among dead hosts strengthens interpretations of previous work correlating Arsenophonus with poor health outcomes in bees [44,45,91]. HT is considered to increase the scope for the evolution of virulence [17,18], although this trait alone is insufficient to draw conclusions regarding symbiont phenotype, as many avirulent or beneficial microbes are transmitted horizontally [15,92].…”
Section: Discussionsupporting
confidence: 81%
“…An economically important eusocial host, the Western honey bee (Apis mellifera), has previously been associated with Arsenophonus [39][40][41][42][43] and infection has been linked to poor health outcomes [44] including colony collapse disorder [45]. Whilst this interaction has attracted interest from the community, basic information on the epidemiology and transmission of Arsenophonus in honey bee populations is nevertheless lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Strains belonging to Enterobacteriaceae are often associated with gastrointestinal diseases in mammals [ 35 , 36 ]. In the honeybee, the Enterobacteriaceae family is positively correlated with gut dysbiosis [ 33 ] and unhealthy colonies [ 37 ]. In one study on colonies suffering from Colony Collapse Disorder, the abundance of Arsenophonus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The application of endogenous LAB in beekeeping has mainly focused on colony health status, pathogen defence, nutrition and modulation of immune response. Budge et al () analysed the microbiota of different beehives and concluded that Lactobacillus and Leuconostoc were the genera most frequently associated with healthy hives and their strength was measured as the number of bee combs (Budge et al ). On the other hand, it has been reported that the more active the Bifidobacterium community was in bee guts, the lower the activity of pathogen bacteria.…”
Section: Methodsmentioning
confidence: 99%